ANALISIS DINAMIKA KELOMPOKTANI KARET (Hevea brasiliensis) DI KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Lestari, Ayu; Yulida, Roza; ', Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aimed to analyze the dynamics of a rubber farmer groups in XIII Koto Kampar. The method used in this study was a stratified random sampling method. The sampling was done by purposive, the research area intentionally was determined by the consideration that in XIII Koto Kampar have many rubber farmer groups or a direct appointment of farmers belonging to the largest and smallest farmer groups. Data analysis was performed using a Likert scale. Data collected consist of primary data and secondary data obtained through interviews and from relevant agencies. These results indicated that the dynamics of rubber farmer group in XIII Koto Kampar which was seen from the purposes of the group, the group structures, the group functions, the development and the maintenance of the group, the group atmosphere and the pressure groups were included in the criteria of "average" which was shown by the average score 3.28. Keywords: Group dynamics, rubber farmer groups. Â